Laryngoscopic, electroglotographic, acoustic and symptomatic consequences produced by vocal overload in women with healthy untrained voices - Fuentes Aracena, Christopher; Ahumada García, Felipe; Arce Valiente, Carlos; Arias Acevedo, Jorge; Moya Cortés, Pablo (Revista de Investigación en Logopedia, 2021)
Overload is one of the stages of vocal load continuum. Currently, its research is considered to allow a better understanding of the pathology and functional symptomatology of the voice. The objective of this work was to analyse the laryngoscopic, electroglotographic, acoustic and symptomatic consequences produced by vocal overload in women with healthy untrained voices. The acoustic, laryngoscopic, electroglotographic and symptomatological behaviour of 30 women was examined, who were subjected to a task of vocal overload consisting of the uninterrupted reading of a text for 60 minutes, whose intensity ranged between 75 and 85 dB. At the laryngoscopic level, greater vascularisation, increased supraglottic compression and changes in the amplitude, symmetry and mucosal wave were observed. At the acoustic level, a significant increase in the fundamental frequency and vocal intensity was evidenced. In the electroglottography (EGG), the closed quotient as well as the open and closed phases decreased significantly; while at the symptomatic level, the total sample experienced at least one symptom of vocal fatigue. In conclusion, findings observed are expressions of both fatigue on the thyroarytenoid mechanism and acute inflammation of the vocal fold cover.